Structure-guided engineering of TGF-βs for the development of novel inhibitors and probing mechanism - Hinck, Andrew P. (Bioorg Med Chem, 2018)
The increasing availability of detailed structural information on many biological systems provides an avenue for manipulation of these structures, either for probing mechanism or for developing novel therapeutic agents for treating disease. This has been accompanied by the advent of several powerful new methods, such as the ability to incorporate non-natural amino acids or perform fragment screening, increasing the capacity to leverage this new structural information to aid in these pursuits. The abundance of structural information also provides new opportunities for protein engineering, which may become more and more relevant as treatment of diseases using gene therapy approaches become increasingly common. This is illustrated by example with the TGF-β family of proteins, for which there is ample structural information, yet no approved inhibitors for treating diseases, such as cancer and fibrosis that are promoted by excessive TGF-β signaling. The results presented demonstrate that through several relatively simple modifications, primarily involving the removal of an α-helix and replacement of it with a flexible loop, it is possible to alter TGF-βs from being potent signaling proteins into inhibitors of TGF-β signaling. The engineered TGF-βs have improved specificity relative to kinase inhibitors and a much smaller size compared to monoclonal antibodies, and thus may prove successful as either as an injected therapeutic or as a gene therapy-based therapeutic, where other classes of inhibitors have failed.